Functional analysis of Borrelia burgdorferi uvrA in DNA damage protection - Sambir, Mariya (2011)
Bacterial pathogens face constant challenges from DNA-damaging agents generated by host phagocytes. Although Borrelia burgdorferi appears to have many fewer DNA repair enzymes than pathogens with larger genomes, it does contain homologues of uvrA and uvrB (subunits A and B of excinuclease ABC). As a first step to exploring the physiologic function of uvrA(Bbu) and its possible role in survival in the host in the face of DNA damaging agents, a partially deleted uvrA mutant was isolated by targeted inactivation. While growth of this mutant was markedly inhibited by UV irradiation, mitomycin C (MMC) and hydrogen peroxide at doses which lacked effect on wild-type B. burgdorferi, its response to pH 6.0 – 6.8 and reactive nitrogen intermediates was similar to that of the wild-type parental strain. The sensitivity of the inactivation mutant to UV irradiation, MMC and peroxide was complemented by an extrachromosomal copy of uvrA(Bbu). We conclude that uvrA(Bbu) is functional in B. burgdorferi.